Impact of Momordica charantia (karela) on serum aspartate aminotransferase level in streptozotocin induced diabetic rats - Mohal, S; Mondal, DK; Chowdhury, PK; Biswas, H; Khanom, A; Shamim, KM (Mediscope, 2015)
The present experimental study was conducted to investigate whether Momordica charantia (karela) has got any impact on serum aspartate aminotransferase (AST) level in the streptozotocin induced diabetic rats. Sixty healthy young Long Evans rats of male sex weighing 150 to 280 gm aged between 10 to 12 weeks were used in this study. The rats were divided into 4 equal groups depending on their different sorts of dietary feedings and drug treatment. Serum AST level was estimated in all rats up to day 51 from the day of streptozotocin/ vehicle injection. The mean ± SD of final serum AST level as percentage of corresponding initial level (value on 51st day to the value on 7th day) was 95.1 ± 13.4 u/L in healthy rats, 110.0 ± 7.6 u/L in the untreated diabetic rats, 39.4 ± 10.1 u/L in the insulin-treated diabetic rats and 109.5 ± 23.8 u/L in the karela-treated diabetic rats. The AST percentage change value of diabetic rats on 51st day corresponding to the initial on 7th day was significantly higher than that healthy rats (p < 0.01). The value in the insulin-treated diabetic rats was significantly lower than that of the untreated diabetic rats (p < 0.001) and the karela-treated diabetic rats (p < 0.001). There was no significant difference between the values of the untreated diabetic rats and the karela-treated diabetic rats (p > 0.05). Karela showed a tendency of acting against hyperglycemic effects of streptozotocin induced diabetes mellitus and also acting against high serum aspartate aminotransferase (AST) level in streptozotocin induced diabetes mellitus. However, further investigations are recommended for establishing karela as a safe and useful effective anti-hyperglycemic agent as well as an agent acting against the rise in serum AST level in streptozotocin induced diabetic rats. Mediscope Vol. 2, No. 1: 2015, Pages 18-21